Kuala Pahang Seafood Complex: Fisheries based products and restaurant as preferred destination and tourism attraction - Ishak, Ismail; Hasnah, Haron; Darun, Mohd Ridzuan; Noor Azlinna, Azizan; Abdul Shukur, Ishak; Wan Khairul Anuar, Wan Abd Manan; Shamsudin, Norazidah (2017)
University Malaysia Pahang (UMP) has been entrusted by the East Coast Economic Region (ECER) Malaysia to advance the local area of Kuala Pahang Seafood Complex as a preferred destination of fisheries-based products and seafood restaurant in Malaysia by local, domestic and foreign tourists. Thus, this research project was conducted to develop and suggest the possible concept and business model for Kuala Pahang. Site visit, interviews and survey using research questionnaire had been conducted in this case study. According to the survey and interviews conducted, the potential to attract customers and visitors is highly anticipated for this Kuala Pahang Seafood Complex. This project is perceived to increase the standard of living for local people through income generation opportunity while contribute for the socio-economic development of Pahang state and Malaysia as a whole. Various activities and strategies are recommended in order to develop the area where the collaboration of various parties including government agencies, state agencies, tourism agencies, restaurants’ owners and locals is very crucial to achieve all the key factors of the strategy.